PENGARUH LEMBAR KERJA PESERTA DIDIK TERINTEGRASI MATERI KABUT ASAP TERHADAP KOMPETENSI PESERTA DIDIK PADA MATERI SUHU, KALOR DAN OPTIK DALAM MODEL PEMBELAJARAN COOPERATIVE PROBLEM BASE LEARNING DI KELAS X SMAN 2 PADANG - Delima Putri; Ahmad Fauzi; Letmi Dwiridal (Universitas Negeri Padang, 2016)
Lack of motivation in learning is one of the factors causing low competens of learners. Motivation of students can be increased through contextual learning, authentic, as well as close to the lives of learners. That matter can be done by integrated real problems and issues which is growing into the learned process. The problem can be integrated form of natural disasters such as smog. Ability of troubleshooting can be improved through learning used the problem base learning model. One of them is cooperative problem base learning. There two purpose of this research is : 1) to investigate whether the influences of LKPD Which Means integrated fog material immediately Against Competence Learners 2) investigated contribution of LKPD which is integrated smog for the competence of learners. Operational research is a quasi-experimental design with randomized control group study design only. The population of research is all member learners levels X MIPA registered even on semester of Academic Year 2015/2016. Samples were taked using cluster random sampling technique. Research data is competence of learners at knowledge, attitude, skill competence and the value of LKPD integrated smog. The instruments for measured knowledge competence is final test, for measured attitude competence is observation sheet and for measured skill competence is work method assessment sheet. Research data were analyzed with prayer equality test average and regression test and correlation. Prayer equality test performed on average to review rated kompetence learners both classes. Regression and correlation performed to review rated kompetence learners with LKPD value. Results showed differences are average value of both class the significant between each kompetence samples for review, where the experimental classes have an average of more high. Through correlation gained significance level of competence penegatahuan relationship value value LKPD was enough with strong, with fg contributions LKPD 45.42%. Competence values relationship significance attitude with LKPD value is strong, with fg LKPD contribution of 62.92%. Values relationship skills kompetence significance with LKPD value is strong, with fg LKPD contribution of 78.58%.